EVALUASI MEDAN UNTUK PERMUKIMAN DI KECAMATAN TUGU DAN NGALIYAN KOTA SEMARANG - Sriyono Sriyono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
The study was done at Tugu and N galiyan District, Semarang City, Central Java. The aim of study (a) to find out the terrain suitability classes for settlement in the research area, (b) to evaluate the terrain for a settlement site (in this case for housing) in the research area based on their terrain suitability for settlement, and (c) to determine the dominant variables influencingthe defferent classes of terrain suitability for settlement. The terrain units as analyse units were established based on the results of maps overlayed of the geomorphological map, the geological map, the slope steepnees map and the soil type map. The physical characteristics of the terrain units were analyzed based on the variables of other terrain suitability for settlement, consisted 17 variables have been established: they were slope steepnes, index of plasticity, soil texture, force induration of rock, rough material, drainage, soil permeability, erosion, flood, ground water, etc. In order find out the classes of terrain suitability, each variable in each terrain units had been constructed by rating technique, will made a map of terrain suitability for settlement. To evaluate the terrain on housing locations. a map of terrain suitability of settlement was overlayed with housing sites map on research area by using computer based Geographical Information System (GIS) aided by Arc Info and Arc View software. In order to find out the dominant influence variables to the defferent levels ofter rain suitability for their settlement had been analyzed with statistical (multiple regression). The result, of the study indicate that : First, there are only 2 variations in the terrain qualities being studied, these are reflected by medium level (medium class) of terrain sutability for an area of 54.0524 square kilometers or 72.33 % of the total area and low level (bad class) of terrain suitability for an area of 20.6822 square kilometers or 27.67% of the total area. The hypothesis that "terrain unit on the landfonn of denuded structurally hill will have low level (bad class) of terrain suitability for sttlement sites" was rejected. Second, The housing sites being studied are generally located in the terrain units with medium levels for an area 354 hectares or 79.37 % of the total housing sites on the research area. The hypothesis that "most of the housing sites in the area being studied, are located in terrain unit with low levels (bad class) of terrain suitability for settlement" was rejected. Third, the surface drainage is the dominant variables influencing the levels terrain suitability for settlement.